2014
DOI: 10.1152/jn.00553.2013
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant synchrony in the somatosensory cortices predicts motor performance errors in children with cerebral palsy

Abstract: Cerebral palsy (CP) results from a perinatal brain injury that often results in sensory impairments and greater errors in motor performance. Although these impairments have been well catalogued, the relationship between sensory processing networks and errors in motor performance has not been well explored. Children with CP and typically developing age-matched controls participated in this investigation. We used high-density magnetoencephalography to measure event-related oscillatory changes in the somatosensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 39 publications
5
60
1
5
Order By: Relevance
“…128 More recent work in this area has examined the oscillatory dynamics of somatosensory processing, and these studies have shown that children with CP have abnormal neural synchronization within sensorimotor cortices following tactile stimulation of the foot. 129-130 Specifically, children with CP exhibited decreased synchronization in the theta-alpha range (4-14 Hz) in response to tactile stimulation, whereas typically-developing controls showed robust increases in theta-alpha synchronization in the same medial sensorimotor cortices. 129 Interestingly, the strength of neural synchronization in the somatosensory cortices, induced by tactile stimulation, has also been connected to ankle strength, step length, and walking speed in children with CP, which suggests a direct connection between these sensory processing measures and motor performance.…”
Section: Cerebral Palsy (Cp)mentioning
confidence: 99%
“…128 More recent work in this area has examined the oscillatory dynamics of somatosensory processing, and these studies have shown that children with CP have abnormal neural synchronization within sensorimotor cortices following tactile stimulation of the foot. 129-130 Specifically, children with CP exhibited decreased synchronization in the theta-alpha range (4-14 Hz) in response to tactile stimulation, whereas typically-developing controls showed robust increases in theta-alpha synchronization in the same medial sensorimotor cortices. 129 Interestingly, the strength of neural synchronization in the somatosensory cortices, induced by tactile stimulation, has also been connected to ankle strength, step length, and walking speed in children with CP, which suggests a direct connection between these sensory processing measures and motor performance.…”
Section: Cerebral Palsy (Cp)mentioning
confidence: 99%
“…The mechanism underlying the group differences in LAVar is likely the atypical temporal and spatial coding of the neural commands to muscles necessary for fluent speech production (Smith, 1989) and not orofacial characteristics such as bone mass or muscle physiology (Walsh & Smith, 2013). Possible sources for the higher movement variability of CWS-Per include variability in motor planning (Churchland, Afshar, & Shenoy, 2006) and execution (Smith, 1989), aberrant neural synchrony and deficits in the use of sensory feedback (Kurz, Heinrichs-Graham, Arpin, Becker, & Wilson, 2013), and the amount of neuromotor noise during movement execution (Harris & Wolpert, 1998). Neuromotor noise arises from brain areas responsible for motor planning and execution, and may fluctuate due to movement complexity, cognitive-linguistic load, and other stressors (Churchland et al, 2006;Van Beers, Haggard, & Wolpert, 2004;Van Gemmert & Van Galen, 1997).…”
Section: Persistence Of Stuttering At 5-7 Years Of Age Is Associatedmentioning
confidence: 99%
“…Movement variability is also critical for responding to permutations in the environment and producing on-line corrections [44,50,51]. On the other hand, pathologically increased movement variability has been characterized in many neurologic conditions, including Parkinson disease [52][53][54][55][56], stroke [39,57], dystonia [41,58], developmental coordination disorder [59,60], and cerebral palsy [61,62], to name a few.…”
Section: Introductionmentioning
confidence: 99%